Push-out bond strength of glass fiber posts luted with two resin cements - Léon, Blanca Liliana Torres; Franco, Vitor Lopes; Silva, Emily Vivianne Freitas; Muniz, Leonardo; Ribeiro, Fernando Carneiro (Brazilian Dental Science, 2017)
Objective. To evaluate the bond strength of a prefabricated glass fiber post to the root dentin with two resin cements using the push-out test. Material and Methods. Thirty fiber posts (White Post ECD) were cemented in human endodontically treated anterior teeth with two resin cements (n=15): RelyxTM ARC and AllCem. The roots were transversely sectioned and divided in cervical, middle and apical thirds after 48 h of cementation. The specimens’ retention was tested by push-out method. The results were analyzed by 2-way ANOVA and Tukey’s test (p<0.05). Results. There were no significant differences in the bond strength between the resin cements. The bond strength was higher in cervical third than in middle and apical thirds for both resin cements. It was observed higher percentages of adhesive failures followed by mixed. Conclusions. Both resin cements are indicated in the cementation of glass fiber post. Keywords Dental prosthesis; Post and core technique; Biomechanical phenomena.